2009
DOI: 10.1007/s00259-009-1262-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of regional myocardial oxygen metabolism in normal pigs using positron emission tomography with injectable 15O-O2

Abstract: These results indicate that injectable (15)O-O(2) has the potential to evaluate myocardial oxygen metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In particular, using the injectable 15 O-O 2 PET technique in spontaneously hypertensive rats (SHR), this research group clearly demonstrated that hypertension could intensify cerebral metabolic disturbances during the acute phase after the onset of stroke (Figure 2 [15]). This same group also applied the 15 O-O 2 injection technique to miniature pigs to evaluate myocardial oxygen metabolism, which was also considered to be a difficult target for evaluation by 15 O-O 2 gas inhalation because of the existence of radioactivity spillover from the gas volume in the lung to the myocardium due to limited spatial resolution [17]. Although the blood-based injectable 15 O-O 2 system provided a strong option that enabled oxygen metabolism measurement in small animals under normal and pathological conditions, some drawbacks were addressed for further applications.…”
Section: Intravenous Administration Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, using the injectable 15 O-O 2 PET technique in spontaneously hypertensive rats (SHR), this research group clearly demonstrated that hypertension could intensify cerebral metabolic disturbances during the acute phase after the onset of stroke (Figure 2 [15]). This same group also applied the 15 O-O 2 injection technique to miniature pigs to evaluate myocardial oxygen metabolism, which was also considered to be a difficult target for evaluation by 15 O-O 2 gas inhalation because of the existence of radioactivity spillover from the gas volume in the lung to the myocardium due to limited spatial resolution [17]. Although the blood-based injectable 15 O-O 2 system provided a strong option that enabled oxygen metabolism measurement in small animals under normal and pathological conditions, some drawbacks were addressed for further applications.…”
Section: Intravenous Administration Methodsmentioning
confidence: 99%
“…The length of the artificial lung was 6 cm in the original report [13] and was changed to 18 cm in the latter studies for improvement of labeling efficiency [14, 15, 17]. …”
Section: Figurementioning
confidence: 99%
“…Radioprobes derived from low-molecular-weight polypeptides or compounds, small recombinant antibody fragments (Fab, scFv), engineered variants (diabodies, triabodies, minibodies, and single-domain antibodies), or pretargeting antibody methods show rapid clearance of radioactivity from the circulation (19)(20)(21). Image-subtraction techniques (22)(23)(24) or kinetic model analysis (25,26) may also help solve this issue. Accordingly, 99m Tc-TF-mAb or its derivatives have great potential as in vivo molecular imaging probes and deserve further investigation.…”
Section: Limitations Of 99m Tc-tf-mabmentioning
confidence: 99%
“…Consequently, we found that hypertension intensifies metabolic disturbances after the onset of strokes. [90][91][92][93] Thus injectable 15 O-O 2 could be used reliably to estimate oxygen metabolism in an infarction rat model with PET. Furthermore, we developed molecular probes for nuclear medicinal imaging targeting β-secretase in the brain, acetylcholine esterase, cyclooxygenase-2 (COX-2), epidermal growth factor receptor (EGFR), and hepatic organic anion transporter (OATP1B1).…”
Section: Tc or 186/188mentioning
confidence: 99%